2008
DOI: 10.1080/02607470801979558
|View full text |Cite
|
Sign up to set email alerts
|

Boys' ‘underachievement’ and the feminization of teaching

Abstract: In England, Scotland and other countries, policy-makers often depict the targeted recruitment of men to the teaching profession as a panacea for male underachievement and disaffection from school. It is commonly assumed that the gender gap in achievement stems from the dearth of male role models in teaching, especially at primary level. Giving particular attention to recent literature on the influence of teacher gender on classroom interaction and educational outcomes, the paper begins by scrutinizing the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 27 publications
2
59
1
3
Order By: Relevance
“…The call for more male role models has often been linked in problematic ways to a moral panic about the underachieving boy and the feminisation of teaching (for a critique of this position, see Carrington and McPhee 2008;Carrington, Tymms, and Merrell 2008 ;Mills, Martino, and Lingard 2004). Significant literature in the field has highlighted the extent to which such concerns have led to the male teacher emerging as central to a project of re-masculinisation that is designed to rehabilitate boys' damaged or failing masculinities, as a consequence of the increasing feminisation of elementary schooling (see Carrington 2002;Martino 2008;Skelton 2002).…”
Section: Background and Analytic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The call for more male role models has often been linked in problematic ways to a moral panic about the underachieving boy and the feminisation of teaching (for a critique of this position, see Carrington and McPhee 2008;Carrington, Tymms, and Merrell 2008 ;Mills, Martino, and Lingard 2004). Significant literature in the field has highlighted the extent to which such concerns have led to the male teacher emerging as central to a project of re-masculinisation that is designed to rehabilitate boys' damaged or failing masculinities, as a consequence of the increasing feminisation of elementary schooling (see Carrington 2002;Martino 2008;Skelton 2002).…”
Section: Background and Analytic Frameworkmentioning
confidence: 99%
“…Such policy-related critique and empirical research have drawn attention to the fallacious assumptions at the basis of the call for more male teachers in elementary schools, as well as the problem of failing to engage with research-based literature about the impact and effects of hegemonic masculinities on male teachers' lives in schools (see Ashley 2003;Carrington and McPhee 2008;Francis 2008;Pepperell and Smedley 1998;Skelton 2002Skelton , 2003. In addition, more specific research, focusing on students' accounts of effective teaching, has found that there is no empirical basis for the claims that male teachers or rather that the gender of the teacher per se is a factor that enhances students' learning or motivation in school (see Lahelma 2000;Lingard et al 2002).…”
Section: Background and Analytic Frameworkmentioning
confidence: 99%
“…Necesitamos involucrar a los chicos, a través de un buen manejo de sus intereses, en las discusiones en clase y las discusiones en parejas o pequeños grupos, en la narración de cuentos y en la lectura en voz alta, eligiendo materiales que puedan resultar de su interés. Asimismo, es importante que los chicos puedan disponer de hombres como modelos positivos de lectura, ya que parece que estos, a menudo, consideran la lectura como una "actividad que no mola" o es "poco masculina" (Carrington y McPhee, 2008).…”
Section: Discusión Y Conclusionesunclassified
“…For some anti-feminist writers, the comparative shortfall in boys' achievement is linked to the embedding of 'feminine' attributes of anti-competition across the curriculum and the often perceived feminised character of teaching and learning strategies more generally (Carrington & McPhee, 2008;Francis, 2000;Harris, 2004;Pollack, 1999). Such a view can be traced through a Sunday Times article in which Minette Marrin (2010) argues that education discourses and practices have been co-opted by a set of feminist sensibilities and values -a peculiar offshoot of the 1980s feminist-inspired drive to improve the personal and academic success of female learners.…”
Section: Introductionmentioning
confidence: 97%